2021
DOI: 10.3390/jcm10122676
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Carotid Corrected Flow Time to Predict Fluid Responsiveness in Patients Mechanically Ventilated Using Low Tidal Volume after Surgery

Abstract: Predicting fluid responsiveness in patients under mechanical ventilation with low tidal volume (VT) is challenging. This study evaluated the ability of carotid corrected flow time (FTc) assessed by ultrasound for predicting the fluid responsiveness during low VT ventilation. Patients under postoperative mechanical ventilation and clinically diagnosed with hypovolemia were enrolled. Carotid FTc and pulse pressure variation (PPV) were measured at VT of 6 and 10 mL/kg predicted body weight (PBW). FTc was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 35 publications
0
40
1
Order By: Relevance
“…In our study, the AUROC of the ΔFTc bolus was 0.935, and the cutoff value was 0.725 with a sensitivity of 97.1% and specificity of 84%. The AUROC was higher than that was reported by Jung et al (46).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In our study, the AUROC of the ΔFTc bolus was 0.935, and the cutoff value was 0.725 with a sensitivity of 97.1% and specificity of 84%. The AUROC was higher than that was reported by Jung et al (46).…”
Section: Discussioncontrasting
confidence: 82%
“…However, there is a relative lack of research on predicting fluid responsiveness in mechanically ventilated patients with a tidal volume < 8 mL/kg PBW while preserving spontaneous breathing, particularly regarding FTc and Δ V peak. Jung et al (46) indicated that in postoperative patients, carotid artery FTc at VT = 6 mL/kg PBW (0.897, P < 0.0001, 95% CI: 0.750–0.973) performed better in predicting fluid responsiveness than PPV at VT = 10 mL/kg PBW (0.867, P < 0.0001, 95% CI: 0.712–0.957). The study used the absolute value of carotid artery FTc.…”
Section: Discussionmentioning
confidence: 99%
“…So, in recent times there has been considerable interest in using carotid ultrasound for predicting fluid responsiveness [7, 10-15, 17,18, 20-22]. These papers studied carotid corrected flow time [7, 10,14,15,17,18,22] changes in peak velocity [11-13, 17, 18, 20, 21] or carotid blood flow [22] to predict fluid responsiveness. Since most of the available studies used carotid corrected flow time or changes in peak velocity, we decided to use those two parameters for our systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved. Studies using carotid corrected flow time have used either Bazett's [10,18] or Wodey's [10,[14][15]17] formulas for assessing FTc. Bazett's formula is calculated by dividing the flow time with square root of cycle time while Wodey's formula gives FTc as measured flow time + [1.25 (heart rate -60].…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] The single systematic review and meta-analysis investigating solely mechanically ventilated adult patients is itself limited by a low number of included studies. 39 Since the 2018 publication of this review, 8 more relevant studies [40][41][42][43][44][45][46][47] have been performed.…”
mentioning
confidence: 99%